AGENCY THEORY: OWNERSHIP STUCTURE AND CAPITAL STRUCTURE AS DETERMINANTS OF DIVIDEND POLICY - Anggoro, Haris Dwi; Yulianto, Arief (Management Analysis Journal, 2019)
The purpose of this study is to analyze the effect of ownership structure and capital structure in decision-making about dividend policy. Observation units used in this study consisists off all manufacturing companies listed on the Indonesia Stock Exchange which pay dividend during 2008 to 2017. This research uses purposive sampling method. The number of samples in this study was 21 companies consist of 210 data. The research variables consist of Institutional Ownership, Public Ownership and Capital Structure as independent variables and Dividend Policy as the dependent variable. Data analysis method used is descriptive analysis, determinan of panel data estimation model, multiple linear regression with Eviews 9. The result of this study shows that institutional ownership and public ownership has a negative effect and significant to the dividend policy. Capitsal structure has a positive but not significant to the dividen policy.